Comparison of Karyotypes in Two Hybridizing Passerine Species: Conserved Chromosomal Structure but Divergence in Centromeric Repeats - Poignet, Manon; Johnson Pokorná, Martina; Altmanová, Marie; Majtánová, Zuzana; Dedukh, Dmitry; Albrecht, Tomáš; Reif, Jiří; Osiejuk, Tomasz S.; Reifová, Radka (Frontiers in Genetics, 2021)
Changes in chromosomal structure involving chromosomal rearrangements or copy number variation of specific sequences can play an important role in speciation. Here, we explored the chromosomal structure of two hybridizing passerine species; the common nightingale (Luscinia megarhynchos) and the thrush nightingale (Luscinia luscinia), using conventional cytogenetic approaches, immunostaining of meiotic chromosomes, fluorescence in situ hybridization as well as comparative genomic hybridization (CGH). We found that the two nightingale species show conserved karyotypes with the same diploid chromosome number of 2n=84. In addition to standard chromosomes, both species possessed a small germline restricted chromosome of similar size as a microchromosome. Just a few subtle changes in chromosome morphology were observed between the species, suggesting that only a limited number of chromosomal rearrangements occurred after the species divergence. The interspecific CGH experiment suggested that the two nightingale species might have diverged in centromeric repetitive sequences in most macro- and microchromosomes. In addition, some chromosomes showed changes in copy number of centromeric repeats between the species. The observation of very similar karyotypes in the two nightingale species is consistent with a generally slow rate of karyotype evolution in birds. The divergence of centromeric sequences between the two species could theoretically cause meiotic drive or reduced fertility in interspecific hybrids. Nevertheless, further studies are needed to evaluate the potential role of chromosomal structural variations in nightingale speciation.